ANALISIS STARTING GAS TURBINE GENERATOR DENGAN STATIC FREQUENCY CONVERTER (SFC) PT. INDONESIA POWER GRATI POMU MENGGUNAKAN SIMULINK MATLAB - Anggie Alvionita; Teguh Utomo; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2022)
Generator is one of the important equipment in a generating system seeing their role as the initial driver. In development and with the aim of efficiency, namely without using a lot of additional equipment, the main generator that has been connected to the compressor and turbine can be selected and used as a replacement for the previous components by means of, the generator is converted into a motor using a Static Frequency Converter (SFC) to then function as a starting drive. Static Frequency Converter (SFC) connects the generator input terminal with the supply from the outside network and then adjusts the rotation during the generator starting process. The main generator which is a synchronous generator is converted into a synchronous motor as a starter motor. Static Frequency Converter (SFC) consists of a rectifier circuit and an inverter where in the starting process the circuit acts as an AC-DC and DC-AC converter. The initial value used for simulation using Simulink Matlab R2021b software is in accordance with the technical data of static starter block 3 PT. Indonesia Power Grati POMU. Based on the results of calculations and simulations, it shows that the use of a Static Frequency Converter (SFC) by inducing the generator into a motor reaches 2300 rpm in the 28th second with the efficiency level reaches 52,551% and an average power used is 71,711W. Keywords: Generator, Static Frequency Converter (SFC), starting device